The Formation of the Brazilian Export-Oriented Pastoral Agro-Industry: State, Agrarian Employers’ Associations, and World Market in the First Republic (London Journal of Research In Humanities and Social Sciences, 2026)
Our doctoral dissertation demonstrates that the export-oriented pastoral agro-industry in  Brazil began growing in the 1920s, shaped by two continuous and interconnected trends.  Exogenously, it stemmed from transformations in the global economy following the late  nineteenth century, particularly the expansion of capital exports and consolidation of  monopolies in core countries. On the other hand, it was also propelled by the  diversification of investments originating from large coffee capital. As shown in the  dissertation, the Brazilian agro-export model produced an economy marked by  dependence, association, and subordination. We have examined the political mediation  exercised by the Rural Society in shaping and advancing the national development project  that ultimately materialised through the alliance between major domestic capital and  international capital.In this vein, our research examines the First Republic—particularly the 1920s—by  analysing the political mediation exercised by the period’s most influential agrarian  employers’ association, the Brazilian Rural Society (SRB), and its role in shaping the  national project for Brazil’s export-oriented livestock agribusiness. To do so, the scope  of inquiry must be widened beyond Brazil’s borders to consider the international  networks forged by the SRB across the Southern Cone, particularly its interactions with  counterpart organisations such as the Argentine Rural Society (SRA) and the Rural  Association of Uruguay (ARU). We have conceptualised the SRB as an agrarian interest  group—an arena of power and consensus-building that articulated economic, political,  and ideological interests. By positioning the SRB as a central actor in the development of  the export-oriented livestock complex, we have advanced a novel interpretation of the  political economy of the First Republic.
Keywords: Agrarian Elites; Agro-Industry; brazil; Capital Dependence; Economic History; Export Model; First Republic; Meat Industry; Pastoral Economy; political economy; Rural Society; Southern Cone; world market